Novel drug research and therapeutic strategies targeting tumor metastasis and cancer stem cells - Xie, Sicong; Zhou, Zhiyi; Zheng, Yu; Yu, Chenshuo; Kong, Weihan; Chen, Yushan; Si, Wenzhe; Zhou, Fei; Yang, Zixuan; Ni, Ruoxuan; Chang, Cheng; Zhang, Yang (Frontiers in Pharmacology, 2025)
Cancer metastasis and stem cells (CSCs) drive resistance and most cancer deaths. Novel agents like Thiolatia (PSMD14 inhibitor) suppress metastasis and enhance chemotherapy efficacy. Sulfarotene targets tumor-repopulating cells in liver cancer with low toxicity. PTC 209 utilizes the high affinity of modified hyaluronic acid nanoparticles for colorectal cancer to reverse CSC stemness in colorectal cancer. Platinum hybrids (HY1-Pt, Salvigenin-Pt) overcome resistance through dual mechanisms. Natural compound Cantharidin inhibits metastasis but requires toxicity optimization. These strategies emphasize specificity, nanodelivery, and combination therapies to reduce toxicity and resistance, highlighting precision oncology potential. Clinical validation remains critical for translation.